Pelatihan Dan Pendampingan Daring Dalam Rangka Peningkatan Literasi Keuangan Praktek Mandiri Bidan Di Kecamatan Sukasada - Luh Gede Kusuma Dewi; Luh Ari Arini; Putu Riesty Masdiantini (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2020)
The midwives profession are expected to have an entrepreneurial spirit, therefore the Midwives Independent Services is one of the micro, small and medium enterprises (MSMEs) that runs in generating profits to cover operational activities and career development. Every business cannot be separated from financial recording activities. This is a control in the progress of the business being carried out. Based on the results of interviews and observations, there are still many of them that do not carry out financial records properly according to SAK EMKM. Therefore, the impact that has been felt by them is ignorance of the services that have been carried out to generate profits or not. Based on these circumstances, it is necessary to have training and mentoring to improve The midwives financial literacy. The training and mentoring online activities were greeted with enthusiasm from the midwives who have a Midwives Independent Practice business in Sukasada District. The topic presented in the training activities was knowledge about midwifery in the era of the industrial revolution 4.0; Income Tax for Midwives; and Improving Midwives' Financial Literacy through the LAMIKRO Financial Application. The topic provided at mentoring sessions are the use of the LAMIKRO application; Introduction to Financial Transactions; Midwives Independent Practice Financial Case I; and Midwives Independent Practice Financial Case II. Based on the results of the pre-test and post-test, there was an increase in the knowledge of the midwives after implementing the training. And based on the questionnaire distributed, the midwives who participated in the training and mentoring activities felt the benefits of this activity and wanted more intensive training for the next opportunity. The midwives also suggested the development of a more detailed financial transaction application specifically for their health service businesses.